The gaps between return forecasted by using traditional CAPM and dynamic CAPM with the actual return: evidence from insurance industry in Malaysia / Muhammad Afiq Abd Hamid - Abd Hamid, Muhammad Afiq (2016)
Capital Asset Pricing Model is a very important model that is used to measure the relationship between risk and expected return that is used in the pricing of a risky security. However, the CAPM model is not always accurate as it often results in wrong predictions. Therefore, This present study examines the deviation between CAPM and DYNAMIC CAPM. For the Dynamic CAPM, it is measured based on the behavioral perspective of the investors, whether they are being rational or irrational. Behavior is measured based on the changes in volume trade. The data of the variables was collected from Bursa Malaysia based on 3 different periods which are before crisis (2004-2007), during crisis (2008-2011), and after crisis (2012-2015) by using 7 companies from insurance industries. Statistical tests included normality, stationarity, and regression test in order to answer the research questions. Findings from the current study suggest that the dynamic CAPM is more accurate than the normal CAPM based on the number of forecasting errors.